2018
DOI: 10.1155/2018/7809305
|View full text |Cite
|
Sign up to set email alerts
|

Nightmare and Abnormal Dreams: Rare Side Effects of Metformin?

Abstract: Background Metformin is widely known as an antidiabetic agent which has significant gastrointestinal side effects, but nightmares and abnormal dreams as its adverse reactions are not well reported. Case Presentation Herein we present a case of 56-year-old male patient with no known history of recurrent nightmares and sleep disorder, experiencing nightmare and abnormal dreams directly after consumption of 750 mg extended release metformin. He reported his dream as an unpleasant experience which awakened him at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…One study reported longer and more efficient sleep among T2D patients on metformin than those using non-metformin agents ( 5 ). In contrast, two other studies found that metformin may be associated with poor sleep quality and frequent nightmares ( 6 , 7 ). In the present study, including 11 806 patients with T2D, we found that those treated with non-metformin were more likely to report difficulty falling and staying asleep at night compared to those without antidiabetic medication use or those on metformin monotherapy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…One study reported longer and more efficient sleep among T2D patients on metformin than those using non-metformin agents ( 5 ). In contrast, two other studies found that metformin may be associated with poor sleep quality and frequent nightmares ( 6 , 7 ). In the present study, including 11 806 patients with T2D, we found that those treated with non-metformin were more likely to report difficulty falling and staying asleep at night compared to those without antidiabetic medication use or those on metformin monotherapy.…”
Section: Discussionmentioning
confidence: 83%
“…Several factors may account for sleep difficulties among T2D patients, including but not limited to comorbidities such as overweight and hypertension (1). As suggested by previous studies, the type of oral antidiabetic agent used to prevent hyperglycemia may also account for sleep difficulties among T2D patients (5)(6)(7). For example, by using one-night sleep polysomnography, a study among 387 outpatients with T2D found that those on metformin slept on average about 36 minutes longer and exhibited a 6.4% higher sleep efficiency compared to patients on non-metformin (mainly sulfonylureas) (5).…”
Section: Introductionmentioning
confidence: 92%
“…Nightmares may be caused by nocturnal hypoglycemia. However, metformin monotherapy does not produce hypoglycemia, particularly in the absence of fasting, malnutrition, vigorous exercise, and advanced age [ 8 ]. Hypoglycemia is uncommon in patients on metformin monotherapy, but Sulfonylureas carry a larger risk of hypoglycemia [ 2 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides knowledge of benefits of glycemic control, weight neutral effects and low risk of hypoglycemia, metformin use during pregnancy remains a matter of concern among physicians 26 . Previous evidence regarding the use of metformin and sleep alterations are mixed: metformin has been linked to improvement of sleep quality 27 and, conversely, was associated with insomnia and nightmares 28 . Presently, only GDM patients had poor sleep quality related to metformin therapy.…”
Section: Discussionmentioning
confidence: 99%